Propostas emergentes: a videoaula como recurso pedagógico no ensino superior - Benetti, Lilian Cervo (2017)
This thesis presents the production of video lessons. Its investigation is aimed to integrate the production of videoconference as a pedagogical resource in higher education, be it presential or at a distance. As a guiding question it was elaborated: systematize a pedagogical project to implement a teacher training workshop with focus on video lessons production in higher educationThis study focuses on educational technologies network for innovation and democratization of the education, and it is part of the research line of Educational Technologies Network Management. The research adopted the typical methodological procedures of Desing-Based Research (DBR). The present research was applied in four phases and three iterative cycles in a context of university professors and postgraduate students training, which was focused on the use of the free software for screen capture Kazam. In a way to collect the data, it was applied diagnostic and evaluation questionnaires, the data registered during the workshop, the workshop design as well the participant’s feedback in relation to the accomplished activities. The first cycle was the application of the questionnaires and the video lessons production workshop in partnership with a search group, GEPETER. After the questionnaire data analysis and the workshop application, was made the redesign for the next application. In the second cycle, it was decided to make the diagnostic questionnaire available online for the post-graduation sectors at the Federal University of Santa Maria. In the third cycle the workshop and the evaluation questionnaire were applied to the group of teachers enrolled in the workshop held via Educational Technology Center. It was obtained, as results, that video lessons production is a pedagogical resource of great audiovisual potential in the teaching and learning processes, which provides changes in the educational context that are mediated by the educational technologies network. The final product for this professional master’s degree is the “Pedagogical Proposal Based on Research: Workshop of video lesson production through free software for screen capture Kazam”. It is a subsidy for managers and educational institutions that intend to invest in teacher training processes to foster pedagogical innovation.